Teacher Evaluation Module for Continuous Improvement in Higher Education - Selena Elizabeth Miranda Gilces (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research is dedicated to the design and development of the teacher evaluation module for the Instituto Superior Tecnológico La Maná, a higher education institution in Ecuador. The purpose is to improve the evaluation process in higher education by leveraging advanced web technologies. This module consists of self-evaluation, co-evaluation, and hetero-evaluation to provide an objective assessment. The resources used include PHP, HTML, CSS, JavaScript, and SQL, which helped speed up processing and improve data accuracy for presenting results through interactive dashboards. The tests conducted demonstrated the system's ability to overcome resource limitations and foster a culture of continuous improvement. The results reflect a positive impact on educational quality by promoting a more collaborative environment.